2020
DOI: 10.1080/02646838.2020.1793308
|View full text |Cite
|
Sign up to set email alerts
|

Emergency C-section, maternal satisfaction and emotion regulation strategies: effects on PTSD and postpartum depression symptoms

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Although there are fewer studies examining PTS in mothers of NNU infants compared to postnatal depression or anxiety, studies have concluded that increased social support is associated with decreased PTS, both for mothers of NNU infants and for postnatal mothers in general [ 25 ]. Similar to current study results, maternal satisfaction with childbirth has been associated with decreased symptoms of postnatal depression, anxiety, and birth-related PTSD in the general perinatal population [ 26 , 27 ]. However, there is a lack of research examining birth satisfaction and postnatal mental health outcomes for parents of infants admitted to NNU.…”
Section: Discussionsupporting
confidence: 87%
“…Although there are fewer studies examining PTS in mothers of NNU infants compared to postnatal depression or anxiety, studies have concluded that increased social support is associated with decreased PTS, both for mothers of NNU infants and for postnatal mothers in general [ 25 ]. Similar to current study results, maternal satisfaction with childbirth has been associated with decreased symptoms of postnatal depression, anxiety, and birth-related PTSD in the general perinatal population [ 26 , 27 ]. However, there is a lack of research examining birth satisfaction and postnatal mental health outcomes for parents of infants admitted to NNU.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the reported mode of birth in the included studies, four studies examined one mode of birth, i.e., vaginal birth [ 36 , 54 , 55 ] or emergency caesarean section (emergency CS) [ 56 ], whereas two studies examined two modes of birth, i.e., vaginal birth and caesarean section (CS) [ 22 , 57 ]. Six studies differentiated between vaginal birth, operative vaginal birth and CS [ 37 , 38 , 58 , 59 , 60 , 61 ], whereas three studies differentiated between vaginal birth, elective caesarean section (elective CS) and emergency CS [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the selected studies, several questionnaires were used to screen for CB-PTS/D. Some were based on the DSM-IV criteria, including the Posttraumatic Diagnostic Scale (PDS) [ 9 , 22 , 38 , 57 , 59 ], PTSD Symptom Scale—self report (PSS-SR) [ 4 , 18 , 68 ], Traumatic Event Scale (TES) [ 36 , 60 , 61 , 66 ], Impact of Event Scale (IES) [ 36 , 58 , 67 ], Posttraumatic Stress Disorder Checklist (PCL) [ 65 ], Post-traumatic checklist scale (PCLS) [ 56 ], and Primary Care PTSD Screen (PC-PTSD-IV) [ 70 ]. The City Birth Trauma Scale (CityBits) [ 62 , 64 , 67 , 69 , 74 ], PTSD-short scale [ 54 ] and Perinatal PTSD Questionnaire (PPQ) [ 37 , 55 , 73 , 75 ] were based on the DSM-V criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations